PEMBELAJARAN IPS DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION DAN THINK PAIR SHARE UNTUK MENINGKATKAN PRESTASI BELAJAR DITINJAU DARI MOTIVASI BELAJAR PESERTA DIDIK DI MTS NEGERI GONDANG SRAGEN TAHUN 2014 - Rukayah, Siti Nur (Jurnal Pendidikan Insan Mandiri, 2016)
This research is aimed to: (1) Examine whether there is difference between Student Teams Achievement Division and Think Pair Share model to the students? achievement. (2) Examine whether there is difference between high, medium, and low level motivation to the students? achievement. (3) Examine whether there is interaction between teaching model and level of motivation to the students? achievement. This research belonged to a true-experimental research with a 3x3 factorial design. The population of this research was all IX grade students of MTsN Gondang Sragen in the first semester of 2014 which consisted of 8 classes. The sample was taken by using purposive sampling. The research sample were IX A, IX C and IX G. From those 3 classes, one class used Student Teams Achievement Division, one class used Think Pair Share, and one class used direct teaching. The total sample consisted of 101 students. The test of instrument used was validity, reliability, item discrimination, and levels of distress. Normality test used Liliefors, Homogeneity test used Barlett and the balance test used F-test. The hypothesis testing used two-way anava with different cell.Based on the hypothesis testing of this research can be concluded that (1) There was difference between Student Teams Achievement Division and Think Pair Share model to the students? achievement. (2) There was difference between the students? high, medium, and low level of motivation to the student?s achievement. (3) There was interaction between teaching model and level of motivation to the students? achievement.  Keywords: Social Learning, Cooperative Learning Model, Student Teams Achievement Division, Think Pair Share, Students? Achievement, Students? Motivation